2019
DOI: 10.1002/anie.201911793
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung Strategy for α‐Functionalization of Aldehydes for the Addition of Thiols and other Nucleophiles

Abstract: Nucleophile-nucleophile coupling is ac hallenging transformation in organic chemistry.Herein we present anovel umpolung strategy for a-functionalization of aldehydes with nucleophiles.T he strategy uses organocatalytic enamine activation and quinone-promoted oxidation to access O-bound quinol-intermediates that undergo nucleophilic substitution reactions.T hese quinol-intermediates react with different classes of nucleophiles.T he focus is on an unprecedented organocatalytic oxidative a-thiolation of aldehydes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 40 publications
1
37
0
2
Order By: Relevance
“…The primary amine 2 b containing a morpholine functionality has been demonstrated to be efficient in inducing high enantioselectivity in organocatalyzed α-functionalisation reactions of α-branched aldehydes. [8] In the chlorination presented herein, this catalyst proved to significantly accelerate the reaction, affording 3 a in 96 % yield after only 2 h with 24 % ee (entry 3). For practical purposes, the enantiomeric excess was determined by transforming 3 a via an S N 2 reaction with thiophenol into the corresponding thioether 4 a (see Supporting Information).…”
Section: Experimental Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…The primary amine 2 b containing a morpholine functionality has been demonstrated to be efficient in inducing high enantioselectivity in organocatalyzed α-functionalisation reactions of α-branched aldehydes. [8] In the chlorination presented herein, this catalyst proved to significantly accelerate the reaction, affording 3 a in 96 % yield after only 2 h with 24 % ee (entry 3). For practical purposes, the enantiomeric excess was determined by transforming 3 a via an S N 2 reaction with thiophenol into the corresponding thioether 4 a (see Supporting Information).…”
Section: Experimental Studiesmentioning
confidence: 78%
“…Given that the predominantly strong acids employed generate anions with a weak basicity, a deprotonation event by such species seems unlikely; 3) a somewhat curious phenomenon has to be considered when catalyst 2 b is applied: Recent work by our group provided evidence, that the morpholine nitrogen is prone to protonation, which changes the steric and electronic properties of the catalyst and thereby its role in the catalytic reaction. [8,14] The possibility of a protonated nitrogen at the morpholine moiety and the potential consequences will be further disclosed in the computational section of this paper. However, a comparison of the pK a -values (0.52 for TFA, 7.38 for N-methylmorpholine in H 2 O) renders the protonation of the catalyst by a strong acid feasible.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Very recently, Jørgensen and co‐workers disclosed the first organocatalytic oxidative α‐thiolation of aldehydes. Instead of an enamine‐electrophile coupling, the authors describe a novel umpolung strategy that allows the activation of aldehydes which can be then paired with different types of nucleophiles, including thiols [20r] . To achieve that, the generated enamine is activated through organocatalysis and quinone‐promoted oxidation to access O‐bound quinol‐intermediates 43 that undergo nucleophilic substitution reactions (Scheme 14).…”
Section: Methods For the Synthesis Of α‐Sulfenylated Carbonyl Compoundsmentioning
confidence: 99%
“…Presently, organocatalysis continues to be a rapidly developing research area, as shown by the large number of publications that have appeared since 2000 [36]. Some recent examples are highlighted in references [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Catalyzed Reactions Under Solvent-free Ball-milling Conditionsmentioning
confidence: 99%